Toward an Active and Stable Catalyst for Oxygen Evolution in Acidic Media: Ti‐Stabilized MnO2. Issue 22 (7th August 2015) - Frydendal, Rasmus; Paoli, Elisa A.; Chorkendorff, Ib; Rossmeisl, Jan; Stephens, Ifan E. L.
Abstract : Catalysts are required for the oxygen evolution reaction, which are abundant, active, and stable in acid. MnO2 is a promising candidate material for this purpose. However, it dissolves at high overpotentials. Using first‐principles calculations, a strategy to mitigate this problem by decorating undercoordinated surface sites of MnO2 with a stable oxide is developed here. TiO2 stands out as the most promising of the different oxides in the simulations. This prediction is experimentally verified by testing sputter‐deposited thin films of MnO2 and Ti–MnO2 . A combination of electrochemical measurements, quartz crystal microbalance, inductively coupled plasma mass spectrometry measurements, and X‐ray photoelectron spectroscopy is performed. Small amounts of TiO2 incorporated into MnO2 lead to a moderate improvement in stability, with only a small decrease in activity. This study opens up the possibility of engineering surface properties of catalysts so that active and abundant nonprecious metal oxides can be used in acid electrolytes. Abstract : A strategy for designing a nonprecious metal catalyst with improved stability for oxygen evolution in acidic electrolytes is presented. Density functional theory calculations suggest that surface titanium on manganese oxide should increase the catalyst stability without affecting the activity. This notion is confirmed experimentally with thin films of Ti–MnO2 .